Al-Tarjih fi Al-Tafsir: antara Makna Al-Qur’an dan Tindakan Manusia - Nurrohim, Ahmad (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2019)
The reflective paper aimed to describe the urgency of the tarjih in the Qur'an interpretation. This study departs from anxiety about role of interpretation in enlighting human actions. The study based on that the Qur’an messages, its commentaries and the human actions should realize circular relations that enlighten each other and continue the dynamics of humanity. It focuses on the urgency of tarjih to enlighten human actions and how the tarjih method developed by interpreters. It is a qualitative descriptive writing by referring various related references, especially in the field of interpretation which is analyzed by the content analysis method. Its result is that the interpretation has an urgent role at theoretical and practical levels in Qur'an understanding. In addition, there are four ways in the tarjih of Qur’an interpretations, namely: tarjih with the Qur'an, tarjih with al-hadith, tarjih with language, and tarjih with context.